2018
DOI: 10.1007/s10495-018-1502-7
|View full text |Cite
|
Sign up to set email alerts
|

A real-time, bioluminescent annexin V assay for the assessment of apoptosis

Abstract: Apoptosis is an important and necessary cell death program which promotes homeostasis and organismal survival. When dysregulated, however, it can lead to a myriad of pathologies from neurodegenerative diseases to cancer. Apoptosis is therefore the subject of intense study aimed at dissecting its pathways and molecular mechanisms. Although many assay methods exist for confirming whether an apoptotic response has occurred in vitro, most methods are destructive and involve laborious operator effort or specialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…Briefly, in this assay, compounds that induce apoptosis will produce time- and dose-dependent increases in luminescence—annexin V fusion protein binding to exposed phosphatidylserine (PS)], which precede temporal increases in fluorescence due to secondary necrosis (loss of membrane integrity). This kinetic difference in the emergence of the signals is the hallmark of an apoptotic phenotype [ 28 ]. Our results from this assay indicated that the apoptotic phenotype of cell death is characteristic of the malignant melanoma A375 cell line, treated with both vanicosides.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in this assay, compounds that induce apoptosis will produce time- and dose-dependent increases in luminescence—annexin V fusion protein binding to exposed phosphatidylserine (PS)], which precede temporal increases in fluorescence due to secondary necrosis (loss of membrane integrity). This kinetic difference in the emergence of the signals is the hallmark of an apoptotic phenotype [ 28 ]. Our results from this assay indicated that the apoptotic phenotype of cell death is characteristic of the malignant melanoma A375 cell line, treated with both vanicosides.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the apoptosis induced in the presence of PFD and PFD-D-Lip, the Real Time-Glo Annexin V apoptosis assay was employed. This assay measures the exposure of phosphatidylserine on the outer leaflet of cell membranes during the apoptotic process through annexin-V binding detected by luminescence, which indicates early apoptosis [52]. It was found that both PFD and PFD-D-Lip (0.5 mg/mL) induced a luminescence signal at the 3-h time point, which increased further until the 6-h time point.…”
Section: Real-time Annexin Apoptosis Assaymentioning
confidence: 99%
“…Due to its subcellular resolution capabilities, optical microscopy methods have shown great promise in identifying, tracking, and studying cell death processes in living cells [9,10]. In particular, several nonlinear optical microscopy techniques have been developed to directly probe the metabolic state of cells with high-sensitivity based on endogenous contrast from metabolic co-enzymes [11].…”
Section: Introductionmentioning
confidence: 99%